(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This article examines direct investments, their role in the development of the country’s economy, and their contribution to the development of the recipient country. Also, the opinions and researches of foreign and local scientists on direct investments and their importance in the development of the country’s economy were studied, real statistical data on the investment environment of the republic were analyzed and a number of recommendations have been developed.